The Effect Of Products, Promotions And Prices On Mizon's Purchasing Decision At Alfamart Sungai Harapan - Fadli; Yandra Rivaldo; Shandrya Victor Kamanda; Edi Yusman (Jurnal Mantik, 2022)
The management of the company always tries and strives to develop its business by selling quality products. The purpose of this study is to determine the influence of products, promotions and prices on purchasing decisions. The population of this study was Mizon consumers in Alfamart Sungai Harapan which amounted to 270 people. The sample consisted of 73 respondents, which were taken bythe accidental sampling method. Data analysis used multiple regression and hypothesis testing and used SPSS version 23. The results of this study concluded that. Product variables, partial, have a significant effect on purchasing decisions. Promotion variables partially have a significant effect on purchasing decisions. Price variables partially have a significant effect on purchasing decisions. Product, promotion and price variables simultaneously have a significant effect on purchasing decisions.